Al-Ghazali’s Refutations of Philosophers: Examining Tahafut al-Falasifah on Eternity, Divine Knowledge, and Resurrection - Juwaini, Juwaini; Zulfian, Zulfian; Mawardi, Mawardi; Safira, Cut Siska (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
Al-Ghazali, a pivotal scholar in Islamic intellectual history, is renowned for his systematic critique of philosophical ideas that challenged Islamic theology during his time. His landmark work, Tahafut al-Falasifah (The Incoherence of the Philosophers), addressed the doctrines of prominent Muslim philosophers such as Al-Farabi and Ibn Sina, who sought to reconcile Greek philosophy with Islamic teachings. Using a library-based research approach and analytical methods, this study examines Al-Ghazali’s refutations, particularly his objections to the concepts of the universe's eternity, God’s limited knowledge of particulars, and the denial of bodily resurrection. By categorizing philosophical thought into acceptable, heretical, and unbelief categories, Al-Ghazali delineated the boundaries of religious orthodoxy in response to these debates. His critical approach not only fortified Islamic theological principles but also established a framework for reconciling reason and faith. This study underscores Al-Ghazali’s enduring influence in Islamic thought and highlights the relevance of his arguments in contemporary discussions on philosophy and religion.